ANALISIS PERSETUJUAN TINDAKAN KEDOKTERAN (INFORMED CONSENT) DALAM RANGKA PERSIAPAN AKREDITASIRUMAH SAKITDI INSTALASI BEDAH SENTRAL RSUD KOTA SEMARANG - Khasna Fikriya; Ayun Sriatmi; Sutopo Patria Jati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Implementation of informed consent is one of the important aspect in assessment elements hospital accreditation. Permenkes RI no. 290 of 2008 set need for informed consent to patients of medical procedure that will be received.Based on preliminary studies on installation central surgery of district hospitalSemarang, many informed consent forms were incomplete and in shortprovision of medical procedures information that given by doctor to patient.This study aimed to analyze implementation of approval medical action (informed consent) in preparation for accreditation at installation central surgery of regional public hospital Semarang as seen from attitude, knowledge and organizational policies which are factors that affect doctor’scompliance to implement informed consent.This type of research is a descriptive qualitative.Data collected through depth interviews with key informants. Then, processing and analysis data. Result showed that doctors know about informed consent and its purpose and function, but lacking knowledge of legal consequences of informed consent. Whereas for attitude, the doctors agreed to obligation of perform informed consent and agree to both rule of law and consequences of implementation of informed consent.But until now, the exists organization's policies, operating procedures, monitoring and sanctions not ensure the doctor’s compliance in applying informed consent.Relation to the preparation of accreditation, there are regulations and implementation of informed consent in hospitals haven’t appropriate with the standards of accreditation. Therefor, it needs a firm and clear arragement with socialization of the informed consent procedure. Also, its necessary for management to develop monitoring and sanctions.